Destined statecraft: Eurasian small power politics and strategic cultures in geopolitical shifts - Wong, Pak-Nung (Springer Singapore Pte. Limited, 2017)
"About the Book" -- "Preface" -- "Acknowledgements" -- "Book Review" -- "Contents" -- "List of Figures" -- "List of Tables" -- "1 Introduction: Remaking the Small Powersâ Destines" -- "Abstract" -- "1.1 The Melian Fate Reconsidered" -- "1.2 The Problem: Destined StatecraftâOptimal Fate-Remaking" -- "1.3 Shifting Poles: Conceptualizing an Emerging Global Order" -- "1.3.1 The âOne Belt One Roadâ Initiative: Background, Goals and Strategies" -- "1.3.2 Existing Approaches of the OBOR Initiative" -- "1.3.2.1 Critical Constructivism" -- "1.3.2.2 Defensive Realism" -- "1.3.2.3 Liberal Institutionalism" -- "1.3.2.4 Global Financial Capitalism" -- "1.3.3 Global Financial Leninism: My Positional Approach of OBOR" -- "1.4 The OBORâs Challenge to the Small Powers: Hypothesis and Questions" -- "1.5 The Key Argument: Destined AgencyâGo with the Flows" -- "1.6 The Habitus Shift in International Relations" -- "1.7 Visualizing the Small Power Politics in Plate Tectonics Imagery" -- "1.8 Book Plan" -- "References" -- "2 The Small Powers in World Politics: Outline of a Theory of African-Asian Critical Realism" -- "Abstract" -- "2.1 Introduction" -- "2.2 Small Power Politics: Theoretical Issues" -- "2.2.1 Major Paradigms of Small Power Politics" -- "2.2.2 Towards an African-Asian Critical Realism" -- "2.2.3 Definition of Small Power Politics" -- "2.3 African and Asian Small Power Politics in Global Context: Empirical Issues" -- "2.3.1 Different Trajectories Towards the Great Power-Hood: USA and China" -- "2.3.1.1 The Making of the Post-cold War US Global Hegemony" -- "2.3.1.2 The Rise of the Post-millennial China as a âGreat Powerâ" -- "2.3.1.3 USA Post-cold War Containment Strategy Towards China" -- "2.3.2 African and Asian Small Power Politics: Liberia and the Philippines".